2002
DOI: 10.3354/meps228143
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic changes in hyposaline tolerance in the mussels Mytilus edulis and M. trossulus: implications for distribution

Abstract: The effect of salinity (5 to 25 ppt) on Mytilus edulis and M. trossulus that co-exist in Atlantic Canada was examined in 2 laboratory experiments. The first experiment tested the effect of salinity on survival and duration of development from fertilization to settlement in the 2 species. Hyposalinity reduced survivorship and percent metamorphosis, and lengthened duration of development. At 5 and 10 ppt, all early stages of both species died. At 25 ppt, > 90% of individuals of both species survived through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 25 publications
5
54
0
1
Order By: Relevance
“…Osmotic stress may 620 have required a large part of this animals' energy budget, leaving no energy for spawning (cf. Qiu et al, 2002;Gillikin et al, 2004). It is also interesting to note that the δ 13 C profiles coincide with changes in [Ba/Ca] shell .…”
Section: High Resolution Barium Profilesmentioning
confidence: 88%
“…Osmotic stress may 620 have required a large part of this animals' energy budget, leaving no energy for spawning (cf. Qiu et al, 2002;Gillikin et al, 2004). It is also interesting to note that the δ 13 C profiles coincide with changes in [Ba/Ca] shell .…”
Section: High Resolution Barium Profilesmentioning
confidence: 88%
“…This difference of up to 1.9 ‰ can alternatively be caused by a summer growth cessation, occurring when ambient water becomes too fresh for the mussels to thrive (Qiu et al, 2002). This certainly seems to be the case in the three shells collected near GF10, and probably in the Akia 10a shell as well.…”
Section: Predicted and Measured Shellmentioning
confidence: 99%
“…It is known that marine bivalves, including M. edulis, have a reduced size and growth rate in low-salinity conditions Westerbom et al, 2002), and that salinities lower than 9.6 are lethal to the mussels within 10 days (Almada-Villela, 1984;Qiu et al, 2002). In response to a sudden drop in salinity, M. edulis withdraws its mantle and siphons, and closes its valves (Qiu et al, 2002). It is likely that the mussels in Godthåbsfjord show this behaviour when exposed to very low salinities and as such cease growing and fail to record large meltwater pulses.…”
Section: Predicted and Measured Shellmentioning
confidence: 99%
“…Further, M. trossulus has been found to inhabit lower salinity areas (Väinölä and Hvilsom 1991;Ridgway and Naevdal 2004;Zbawicka et al 2010Zbawicka et al , 2014Väinölä and Strelkov 2011). Experimental studies have shown that this taxon is less sensitive to lower salinities in the early ontogenetic stages than its congeners (Qiu et al 2002). It is thus hypothesized that the distribution of M. edulis and M. trossulus is influenced greatly by temperature and salinity, with an expectation of a higher frequency of M. trossulus in cold and low salinity waters.…”
Section: Introductionmentioning
confidence: 99%
“…The stratification is caused by melt water from the rivers and glacier runoff of approximately 110 9 10 6 m 3 freshwater, which flows on top of the heavier seawater, creating a stagnant water mass in the bottom of the fiords and thus salinities from 34 down to (Møller 1984). Based on findings of M. trossulus in areas of lower salinities, studies relate this to a higher tolerance to lower salinities compared to M. edulis, a theory that is further backed up by experiments documenting a higher tolerance for M. trossulus at early life history stages (e.g., Qiu et al 2002;Ridgway and Naevdal 2004;Przytarska et al 2010;Zbawicka et al 2014). While the two taxa in most studies are suggested to be physiologically differentiated with respect to salinity, one must bear in mind that areas characterized by lower salinity are also often subjected to significant variation in other environmental factors such as pH, temperature, dissolved oxygen and particulate loadings (Gardner and Thompson 2001), and the proportion of M. edulis vs. M. trossulus may not be solely attributed to a single environmental factor such as salinity.…”
Section: Characteristics Of Greenland Mytilus Populations and Interpomentioning
confidence: 99%